Analisis Hubungan Tingkat Kecemasan Pada Ibu Presectio Caesarea Di Ruang Rawat Inap Kebidanan Rumah Sakit Bhayangkara Palembang Tahun 2017 - Marta, A. Yullius; Zaman, Chairil; Martiandra, Indra (Pengurus Daerah Ikatan Ahli Kesehatan Masyarakat (IAKMI) Provinsi Sumatera Selatan, 2018)
Pregnancy experienced by every woman will certainly cause many problems, both physical and psychological problems. Labor and birth are the physiological processes that accompany the lives of almost every woman. Every woman wants labor to run smoothly and can give birth to a perfect baby. There are two ways of persalian, vaginal delivery and cesarean delivery. This study aims to analyze the relationship of anxiety levels in the mother of Caesarea Presectio in the midwifery room  of Bhayangkara  Hospital Palembang  in 2017. The method  used  in this research  is  Cross-Sectional Study. The population in this study amounted to 72 patients. The sampling technique used in this study is total sampling. Data analysis with univariate, bivariate and multivariate analysis with multiple logistic regression method. Results of univariate analysis were obtained for education 54.8%, parity 54.8%, history of ANC 52.4%, income 45.2% and anxiety 52.4%. The result of bivariate analysis found no relation between income level (p> 0,05). The result of multivariate analysis showed an ANC history related to anxiety in Presectio Caesarea mother. It is recommended for Bhayangkara Palembang hospital to provide information about matters relating to anxiety of presectio caesarea patients so that it can be made into input to perform communication and education to minimize anxiety.